The effect of anaerobic effort on hemoglobin and iron response in the blood serum - Hadeel Tarik Younis Al-Ta ai (مجلة الرافدين للعلوم الرياضية, 2007)
The effect of anaerobic effort on hemoglobin and iron response in the blood serum was studied by taking (10) students of physical education college, University of Mosul / first stage. The procedures of research included a pre- and post-test of 400m running and incompleted post-recovery test (3 minutes) upon the parameters in blood serum (hemoglobin, total iron building capacity (TIBC), serum free iron). The research showed that there was a response in total iron building capacity post-effort test comparing with pre- test. Also, the research showed a response serum iron and total iron building capacity post-recovery comparing with pre- and post-efforts test. But there is no response in hemoglobin.